2019
DOI: 10.1002/pld3.144
|View full text |Cite
|
Sign up to set email alerts
|

COP1 regulates the stability of CAM7 to promote photomorphogenic growth

Abstract: The unique member of the calmodulin gene family, Calmodulin7 ( CAM 7), plays a crucial role as transcriptional regulator to promote Arabidopsis seedling development. CAM 7 regulates the expression of HY 5 , which is intimately involved in the promotion of photomorphogenic growth and light‐regulated gene expression. COP 1 ubiquitin ligase suppresses photomorphogenesis by degrading multiple photomorphogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Although ZBFs were discovered as bona fide Z-box binding proteins, it is increasingly evident that they bind to several cis-acting elements present in the promoters of light, ABA and JA signaling pathway genes and regulate their expression (Boter et al 2004;Mallappa et al 2006;Dombrecht et al 2007;Godoy et al 2011;Singh et al 2012;Gangappa and Chattopadhyay 2013). The protein abundance and nucleo-cytoplasmic shuttling of ZBFs with their interacting partners during Arabidopsis seedling development appeared to be light dependent (Mallappa et al 2008;Kushwaha et al 2008;Senapati et al 2019). Moreover, the varied environmental light signals appear to be the basis for discrimination between different mode (monomer, homodimer, or heterodimer) of transcriptional regulation by the ZBFs (Singh et al 2012).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…Although ZBFs were discovered as bona fide Z-box binding proteins, it is increasingly evident that they bind to several cis-acting elements present in the promoters of light, ABA and JA signaling pathway genes and regulate their expression (Boter et al 2004;Mallappa et al 2006;Dombrecht et al 2007;Godoy et al 2011;Singh et al 2012;Gangappa and Chattopadhyay 2013). The protein abundance and nucleo-cytoplasmic shuttling of ZBFs with their interacting partners during Arabidopsis seedling development appeared to be light dependent (Mallappa et al 2008;Kushwaha et al 2008;Senapati et al 2019). Moreover, the varied environmental light signals appear to be the basis for discrimination between different mode (monomer, homodimer, or heterodimer) of transcriptional regulation by the ZBFs (Singh et al 2012).…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…In a recent study, by using constitutive over-expresser transgenic lines of HY5, a feedback regulatory mechanism of HY5 has been proposed through COP1/SPA ubiquitin ligase system, which is known to degrade HY5 (Osterlund et al 2000;Burko et al 2020). CAM7 has recently been shown to be stabilized by COP1 at lower intensity of light for promoting photomorphogenic growth (Senapati et al 2019). Overexpression of CAM7 in cop1 mutants background enhanced the photomorphogenic growth and caused higher accumulation of chlorophyll and anthocyanin and increased expression of CAB1, RBCS-1A, and CHS1.…”
Section: Zbf1/myc2mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown by a protein microarray study that MKKK20 is able to interact with Calmodulin 7 (CAM7), which is a key transcription factor involved in light signaling pathways. 29 , 30 , 31 , 32 , 33 Further studies have revealed that whereas MPK6 works downstream of MKKK20 in the regulation of osmotic stress, 34 MKKK20 works upstream to MKK3 in the regulation of root growth. 35 The involvement of MKKK20 has been shown in ABA responses.…”
Section: Introductionmentioning
confidence: 99%